STUDI KOLONISASI FUNGI MIKORIZA ARBUSKUAR PADA GAHARU (Gyrinops versteegii) DENGAN SUMBER INOKULAN RIZOSFER PERKEBUNAN GAHARU - I Gde Adi Suryawan Wangiyana; Hidayat Wicaksono; Wahyu Yuniati Nizar (Universitas Muhammadiyah Mataram, 2019)
The aim of this research was to observed the abundance of mycorrhiza spore and mycorrhiza colonization on G. versteegii’s root at agarwood plantation on Langko, Kekait and Pejaring. Rhizosphere samples were taken from 0 cm – 20 cm of depth. Spore extraction was carried by combination of filtration and centrifugation methods. G. versteegii roots were soaked with 10% KOH continued by 2% HCl then were rinsed by distilled water. Lactoglycerol trypan blue 0,05% were used as dye on root colonization observation. Mycorrhiza spore population and root colonization data were analyzed by ANOVA, HSD and Error Standard. Rhizosphere of Pejaring has the highest number of mycorrhiza spore but not significantly different from Rhizosphere of Kekait. Langko rhizosphere has the smallest number of mycorrhiza spore population. On the other hand, this place has the highest mycorrhiza colonization percentage among the others. It could be concluded that Mycorrhiza spore population has negative correlation with mycorrhiza root’s colonization which shows unique symbiotic between mycorrhiza and G. versteegii.